Current targeted therapeutics against COVID-19: Based on first-line experience in China - Zhang, Yue (Pharmacol Res, 2020)
SARS-CoV-2 is a novel strain, causing a global pandemic since the end of 2019. The majority of patients showed nonspecific symptoms such as fever, dry cough, and fatigue. Most patients have a good prognosis while some with severe conditions could rapidly progress to acute respiratory distress syndrome, septic shock, metabolic acidosis, coagulation dysfunction, and even die. The exacerbation of the patient's condition may be due to a cytokine storm in the body. Effective targeted therapies including antiviral and immunization are urgently needed. Although many clinical trials are already underway and the majority of patients have received antiviral therapy based on medication experience with severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), and preliminary results from some clinical trials, there are no antiviral drugs proven to be effective currently. We summarize the current therapeutic medicines used in the clinic, hope to be able to provide some implications for clinical medication.